Targeting β-Cell Plasticity: A Promising Approach for Diabetes Treatment - Esmaeel Ghasemi Gojani; Sweta Rai; Farzaneh Norouzkhani; Salma Shujat; Bo Wang; Dongping Li; Olga Kovalchuk; Igor Kovalchuk (Current Issues in Molecular Biology, 2024)
The β-cells within the pancreas play a pivotal role in insulin production and secretion, responding to fluctuations in blood glucose levels. However, factors like obesity, dietary habits, and prolonged insulin resistance can compromise β-cell function, contributing to the development of Type 2 Diabetes (T2D). A critical aspect of this dysfunction involves β-cell dedifferentiation and transdifferentiation, wherein these cells lose their specialized characteristics and adopt different identities, notably transitioning towards progenitor or other pancreatic cell types like α-cells. This process significantly contributes to β-cell malfunction and the progression of T2D, often surpassing the impact of outright β-cell loss. Alterations in the expressions of specific genes and transcription factors unique to β-cells, along with epigenetic modifications and environmental factors such as inflammation, oxidative stress, and mitochondrial dysfunction, underpin the occurrence of β-cell dedifferentiation and the onset of T2D. Recent research underscores the potential therapeutic value for targeting β-cell dedifferentiation to manage T2D effectively. In this review, we aim to dissect the intricate mechanisms governing β-cell dedifferentiation and explore the therapeutic avenues stemming from these insights.